Phase evolution of Na2O–Al2O3–SiO2–H2O gels in synthetic aluminosilicate binders. Issue 13 (25th February 2016) - Walkley, Brant; San Nicolas, Rackel; Sani, Marc-Antoine; Gehman, John D.; van Deventer, Jannie S. J.; Provis, John L.
Abstract : Nanostructural evolution of Na2 O–Al2 O3 –SiO2 –H2 O gels in synthetic aluminosilicate binders investigated by solid state 29 Si, 27 Al and 23 Na MAS NMR spectroscopy. Abstract : This study demonstrates the production of stoichiometrically controlled alkali-aluminosilicate gels ('geopolymers') via alkali-activation of high-purity synthetic amorphous aluminosilicate powders. This method provides for the first time a process by which the chemistry of aluminosilicate-based cementitious materials may be accurately simulated by pure synthetic systems, allowing elucidation of physicochemical phenomena controlling alkali-aluminosilicate gel formation which has until now been impeded by the inability to isolate and control key variables. Phase evolution and nanostructural development of these materials are examined using advanced characterisation techniques, including solid state MAS NMR spectroscopy probing 29 Si, 27 Al and 23 Na nuclei. Gel stoichiometry and the reaction kinetics which control phase evolution are shown to be strongly dependent on the chemical composition of the reaction mix, while the main reaction product is a Na2 O–Al2 O3 –SiO2 –H2 O type gel comprised of aluminium and silicon tetrahedra linked via oxygen bridges, with sodium taking on a charge balancing function. The alkali-aluminosilicate gels produced in this study constitute a chemically simplified model system which provides a novel research tool for the study of phase evolution and microstructural development in these systems. Novel insight of physicochemical phenomena governing geopolymer gel formation suggests that intricate control over time-dependent geopolymer physical properties can be attained through a careful precursor mix design. Chemical composition of the main N–A–S–H type gel reaction product as well as the reaction kinetics governing its formation are closely related to the Si/Al ratio of the precursor, with increased Al content leading to an increased rate of reaction and a decreased Si/Al ratio in the N–A–S–H type gel. This has significant implications for geopolymer mix design for industrial applications.